The Silenced Voices: Women Online Harassment - Hensman, G.H.; Thasika, Y. (University of Jaffna, 2022)
Online harassment is an increasing problem worldwide and is often gender-based and targeting women and girls. Amid growing threats to women around the world, this research contributes to understanding the phenomenon of women online harassment with a focus on examining the consequences and coping tactics of women. The purpose of the study is to find how do women cope with online harassment and how can online harassment be mitigated? The researchers try to explain the incidents, repercussions of women online harassment through in-depth interviews. Women from various backgrounds were interviewed and three themes were identified using thematic analysis. The three themes are acceptance, self-protection, moral support from family and friends. It is clear that women are very reluctant to share their experiences when it comes to harassment as they feel if they reveal the truth, they are to take a dim view of the society. Additionally, women face a greater burden in deciding if and how to respond to online harassment. Moreover, women expect the society to have a confidential support system. Empowering women via shame management, resilience and emotional intelligence skills will give more alertness to women to escape from online annoyances. The findings highlight how women suppress their emotions when they are harassed via online platforms. Thus, this research provides a brief review of the prevalence and coping tactics of women online harassment.
Keywords: Acceptance; Case examples; Online harassment; Self-protection; Women